Comparative study of halo-vest reduction and skull traction reduction in the treatment of cervical fracture dislocation in patients with ankylosing spondylitis - Wang, Liang; Wang, Haibin; Wang, Can; Zhang, Bangke; Yang, Haisong; Lu, Xuhua (Frontiers in Surgery, 2023)
Background: This study aimed to investigate the safety and efficacy of halo-vest in the treatment of cervical fracture in patients with ankylosing spondylitis (AS). Methods: From May 2017 to May 2021, 36 patients with cervical fractures with AS were included in this study. The patients with cervical spine fractures in AS underwent preoperative reduction by halo-vest or skull tractions. Instrumentation internal fixation and fusion surgery were then performed. The level of cervical fractures, the operative duration, blood loss, and treatment outcomes were investigated preoperatively and postoperatively. Results: A total of 25 cases were in included in the halo-vest group and 11 cases were included in the skull tractions group. The intraoperative blood loss and the surgery duration were significantly less in the Halo-vest group than in the skull traction group. Comparison of ASIA scores at admission and final follow-up showed the neurological function of patients was improved in both groups. All patients had reached solid bony fusion by the follow-up. Conclusion: This study presented a unique approach to halo-vest treatment fixation of unstable cervical fracture in patients with AS. The patient should also have early surgical stabilization with halo-vest to correct spinal deformity and avoid worsening the patient's neurological status.